Impact of HIV Subtype on Performance of the Limiting Antigen-Avidity Enzyme Immunoassay, the Bio-Rad Avidity Assay, and the BED Capture Immunoassay in Rakai, Uganda - Longosz, Andrew F. (Mary Ann Liebert, Inc., 2014)
Previous studies demonstrated that individuals with subtype D HIV infection who had been infected for 2 or more years were frequently misclassified as assay positive using cross-sectional incidence assays. Samples from 510 subjects (212 subtype A, 298 subtype D) who were infected for 2.2 to 14.5 years (median 5.4 years) and were not virally suppressed were tested using an LAg-Avidity enzyme immunoassay (LAg-Avidity EIA), Bio-Rad Avidity assay, and BED capture enzyme immunoassay (BED-CEIA). The performance of these three assays was evaluated using various assay cutoff values [LAg-Avidity EIA: <1.0 OD-n and <2.0 OD-n; Bio-Rad Avidity assay: <40% avidity index (AI) and <80% AI; BED-CEIA: <0.8 OD-n]. The mean LAg-Avidity EIA result was higher for subtype A than D (4.54±0.95 vs. 3.86±1.26, p<0.001); the mean Bio-Rad Avidity assay result was higher for subtype A than D (88.9%±12.5% vs. 75.1±30.5, p<0.001); and the mean BED-CEIA result was similar for the two subtypes (2.2±1.2 OD-n for subtype A, 2.2±1.3 OD-n for subtype D, p<0.9). The frequency of misclassification was higher for individuals with subtype D infection compared to those with subtype A infection, using either the LAg-Avidity EIA with a cutoff of <2.0 OD-n or the Bio-Rad Avidity assay with cutoffs of <40% or <80% AI. No subtype-specific differences in assay performance were observed using the BED-CEIA. Sex and age were not significantly associated with misclassification by any assay. The LAg-Avidity EIA with a cutoff <1.0 OD-n had the lowest frequency of misclassification in this Ugandan population.